2022
DOI: 10.3389/fimmu.2022.989968
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a B cell-related gene pairs signature for predicting prognosis and immunotherapeutic response in non-small cell lung cancer

Abstract: BackgroundAccumulating evidence indicates that the B cells play important roles in anti-tumor immunity and shaping tumor development. This study aimed to explore the expression profiles of B cell marker genes and construct a B cell-related gene pairs (BRGPs) signature associated with the prognosis and immunotherapeutic efficiency in non-small cell lung cancer (NSCLC) patients.MethodsB cell-related marker genes in NSCLC were identified using single-cell RNA sequencing data. TCGA and GEO datasets were utilized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 69 publications
0
3
3
Order By: Relevance
“…Li et al . [41] previously reported a 28-gene signature in TCGA-NSCLC patients with a 3-year AUC of 0.69 in the training dataset, which was lower than the AUC observed in our analysis despite involving more genes. In this study, we found that the response score was significantly associated with immunotherapy response.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Li et al . [41] previously reported a 28-gene signature in TCGA-NSCLC patients with a 3-year AUC of 0.69 in the training dataset, which was lower than the AUC observed in our analysis despite involving more genes. In this study, we found that the response score was significantly associated with immunotherapy response.…”
Section: Discussioncontrasting
confidence: 94%
“…Kaplan-Meier survival analysis in an independent TCGA-LUAD set was also performed, showing an outstanding predictive effect in predicting the prognosis of advanced-stage NSCLC. Li et al [41] previously reported a 28-gene signature in TCGA-NSCLC patients with a 3-year AUC of 0.69 in the training dataset, which was lower than the AUC observed in our analysis despite involving more genes. In this study, we found that the response score was significantly associated with immunotherapy response.…”
contrasting
confidence: 95%
“…The tumor microenvironment is crucial for tumor initiation, progression, and immunity [ 40 ]. Studies have shown that tumor-infiltrating B cells are essential regulators of lung cancer progression [ 41 ]. Under tumor microenvironment signaling, B cells infiltrate, proliferate, and develop within tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Univariate Cox regression analysis of datasets was performed using R’s “ survival ” package for identifying prognostic ARGs, and those ARGs with p < 0.05 were selected ( n = 52). We pairwise compared the relative expression levels of prognostic ARGs in each sample and scored each ARG ( 20 ). ARGs were paired to constitute ARG pairs (ARGPs), including ARG1 and ARG2.…”
Section: Methodsmentioning
confidence: 99%